2007
DOI: 10.1177/230949900701500309
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing for Pathological Femoral Fractures

Abstract: Intramedullary nailing appears safe and effective for treatment of metastatic bone disease, and confers good functional results, pain relief, and mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Allograft reconstructions and plate and screw fixation are not recommended in patients with metastatic bone disease because they require too long to heal, have too many early complications, and add to the complexity of subsequent procedures if metastatic progression occurs 4, 29, 30. Reconstruction‐type, interlocking hip or femoral nails are recommended for femoral pathological fractures, provided that the fracture could be stabilized satisfactorily 4, 20. Closed nailing is usually adequate, except if curettage and cementation of a large cortical defect is to be treated 4.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft reconstructions and plate and screw fixation are not recommended in patients with metastatic bone disease because they require too long to heal, have too many early complications, and add to the complexity of subsequent procedures if metastatic progression occurs 4, 29, 30. Reconstruction‐type, interlocking hip or femoral nails are recommended for femoral pathological fractures, provided that the fracture could be stabilized satisfactorily 4, 20. Closed nailing is usually adequate, except if curettage and cementation of a large cortical defect is to be treated 4.…”
Section: Discussionmentioning
confidence: 99%
“…We observed slightly greater survival rate in our study: 87% of patients survived 89.1 months after surgery. Results of other study demonstrated (15) that postoperative survival rate was did not depend on extent and time of surgery and mostly depended on morphological type of cancer. Considering this, all data should be considered critically.…”
Section: Discussionmentioning
confidence: 93%
“…Bone metastasis at the proximal femur is the third most common site after spine and pelvis [1]. Immediate xation or prosthetic replacement provides pain control, return to previous ambulatory status, improved psychological well-being, and improved quality of life [1][2][3][4][5]. Intramedullary nailing of long bones is an accepted technique for management of existing or impending pathological fracture, especially of the proximal femur.…”
Section: Introductionmentioning
confidence: 99%